Teaching English to Young Learners in China and Ukraine - Haozhe Jiang (Educational Challenges)
The research need is determined by active educational partnership between People's Republic of China and other countries, and Ukraine too. The collaboration promotes the comparative pedagogical researches of educational process of both countries.